Posture and its relationship with falls among older people with low back pain: a systematic review / Zarina Zahari, Nur Fazlin Zainudin and Maria Justine - Zahari, Zarina; Zainudin, Nur Fazlin; Justine, Maria (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Abnormal posture is a common health problem that could lead to fall among older people with low back pain (LBP). Since the incidence of falls among older people is increasing, it is important to identify whether posture abnormality contribute to the risk of falls. This study aimed to determine the posture abnormality that related to falls and to identify the relationship between posture and incidence of falls among older people with LBP. Literature searched was followed PRISMA Guideline. The search included Scopus, PubMed, Clinical Key, PEDro and Google Scholar online databases for studies in English published within 2005 to 2020. McMaster critical appraisal tool was used to assess the quality of the studies. The search retrieved 127 articles however, only 6 were included for review. Five studies showed significant association between posture and falls among older people with LBP while one study was not supported the evidence. Abnormal posture was closely related to falls due to changes in center of gravity that affect postural balance among older people. Thoracic hyperkyphosis, loss of lumbar lordosis, and spino-pelvic alignment seem to contribute to a greater postural instability, and thus to a higher risk of falls in older people with LBP.